PEMANFAATAN DANA WAKAF TUNAI UNTUK PEMBIAYAAN PEMBANGUNAN INRASTRUKTUR - Syafiq, Ahmad (ZISWAF, 2017)
The cash waqf funds can be used for financing the construction of infrastructure projects, since basically the purpose between infrastructure and wakaf development is the same that is to improve the social welfare of the people (ummah). However, since waqf funds belong to the general public handed over to the Waqf Board to be managed, in the inclusion of waqf funds as a source of funds for infrastructure projects development, it is necessary to prioritize prudential aspects so that wakaf funds can again provide sustainable benefits and can be used again for the empowerment of other people